Performance presumptions: a study of ambidexterity, exploration and exploitation on a pharmacy network in Rio Grande do Sul, Brazil (Gestão & Regionalidade, 2017)
The search for managerial strategies that allow the organization to achieve better results has attracted scholars in the field and managers interested in the results of their research. Such interest is due increased competition and volatility of the environment. The research aims to model the ambidextrous actions and their dimensions: exploration and exploitation, in opposition to the performance of the pharmacy network in Rio Grande do Sul, Brazil. The research was based on the quantitative and descriptive research, using the survey method, based on closed questionnaires applied to 612 pharmacies, with a rate of return of 6.53%, that belong to FARXV network. The confirmatory factor analysis and structural equation modeling were used to process the data collected. It was concluded that the investment in ambidextrous strategies, by the companies' managers, results in corresponding performance. Although the association results are also positive, it was not confirmed that the exploration and exploitation strategies result in performance.